Innowacje frazeologiczne w świetle danych korpusowych - Fliciński, Piotr (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
This article aims at highlighting available possibilities offered by web-based language corpuses to support the phraseologist and experts in phraseography in their research methods. From this introduction, the author proceeds to show the ways to keep trace of the changeable character of the phraseological resources in the Polish language in the increasingly democratized cultural space, focusing on the relations between innovative phraseological constructions (neophraseologisms, shifts in meaning and polymorphic type of the form of explicit language usage) and the phraseological norm in modern Polish language. Theoretical considerations are then followed by the analytical part of the article in which the author presents a number of research improvements related to the study of phraseological innovations with the application of the National Corpus of Polish, with three examples provided (powtarzać coś jak mantrę [literally: to repeat something like a mantra], chodzić na rzęsach [to do everything in order to accomplish something, or to make whoopee, to paint the town red] and z prędkością/szybkością karabinu maszynowego – jak karabin maszynowy [to talk a mile a minute]).